ตัวแบบในการพัฒนานวัตกรรมในอุตสาหกรรมฟอกย้อมและตกแต่งสำเร็จสิ่งทอของประเทศไทย - เนตรทราย สุวรรณ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
Textile Dyeing and Finishing Industry is perceived as the major role in adding the textile product value. This research aims to design the innovation development model of textile dyeing and finishing industry of Thailand and evaluate the acceptability of the developed model. Advancement of some factors effecting the innovation of textile dyeing and finishing industry in Thailand had been gathering data from the questionnaires. 80 questionnaires had been spread out and only 30 ones were back. Consisting of in-depth interview for developing a model of innovation development in textile dyeing and finishing industry in Thailand, the data obtained from the questionnaire were sorted out through Cluster Analysis into 3 groups: high, medium and low innovation. Moreover, the results showed that the factors affecting the innovation development in textile dyeing and finishing industry in Thailand in included the performance of product-innovation development activities, the performance of process-innovation activities, the support of innovation development from external agency, the assignment of company’s mission, vision, and strategic goal, and the proportion of innovation and research and development investment. Assessing the developed model acceptance found that the companies accepted the model as being useful to the textile industry development.